2008
DOI: 10.1111/j.1744-7909.2008.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light on the Growth and Clonal Reproduction of Ligularia virgaurea

Abstract: Ligularia virgaurea is a perennial herb that is widely distributed in the alpine meadow on the eastern Qinghai-Tibet plateau. We investigated the patterns of growth and reproduction of L. virgaurea under two contrasting levels of light conditions for two continuous growing seasons. Our results showed that the light effects on the maximum relative growth rate, the shoot weight ratio and the root weight ratio differed between the two growing seasons. L. virgaurea reproduced initially through rhizome in the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
(46 reference statements)
3
16
0
1
Order By: Relevance
“…This indicates that not precipitation per se but a related climatic factor might be the driving force behind the reduced clonality in our wetter transplants. For instance, transplants to more oceanic sites with higher rainfall would also experience an increase in cloudiness, and thus a decrease in light availability, which has been shown to reduce the production of clonal ramets (Guo et al., ; Méthy, Alpert, & Roy, ; Wang, Zhao, Du, & He, ; P. Wang, Lei, Li, & Yu, ; Xie, Zhang, Zhao, Du, & He, ). Our experimental setup allows us to address this effect independent of any change in temperature, which otherwise may have masked this response.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that not precipitation per se but a related climatic factor might be the driving force behind the reduced clonality in our wetter transplants. For instance, transplants to more oceanic sites with higher rainfall would also experience an increase in cloudiness, and thus a decrease in light availability, which has been shown to reduce the production of clonal ramets (Guo et al., ; Méthy, Alpert, & Roy, ; Wang, Zhao, Du, & He, ; P. Wang, Lei, Li, & Yu, ; Xie, Zhang, Zhao, Du, & He, ). Our experimental setup allows us to address this effect independent of any change in temperature, which otherwise may have masked this response.…”
Section: Discussionmentioning
confidence: 99%
“…Although RO is usually discussed as sexual reproductive output, increases in clonal output with size are also common (Brown and Eckert 2005;Hawkins et al 2005;Wang et al 2008). Although clonal output increased with size in the second generation, a surprising result from the first generation of Penthorum sedoides is that stolon and ramet mass decreased as plant size increased.…”
Section: Sexual and Clonal Outputmentioning
confidence: 91%
“…For example, Wang et al (2008) found that RA increased with size across density treatments and decreased in size across sowing dates in Amaranthus retroflexus. Likewise, RA was either positively or negatively correlated with plant size depending on species identity, grazing, and nutrient addition (Niu et al 2009).…”
Section: Sexual Reproductive Allocationmentioning
confidence: 95%
“…; Wang et al. ). However, the effects of light intensity on the relationship between clonal and sexual structures are unknown.…”
Section: Introductionmentioning
confidence: 98%